Ellis Van Creveld2 is Required for Postnatal Craniofacial Bone Development. Issue 8 (2nd May 2016) - Badri, Mohammed K.; Zhang, Honghao; Ohyama, Yoshio; Venkitapathi, Sundharamani; Kamiya, Nobuhiro; Takeda, Haruko; Ray, Manas; Scott, Greg; Tsuji, Takehito; Kunieda, Tetsuo; Mishina, Yuji; Mochida, Yoshiyuki
ABSTRACT: Ellis‐van Creveld (EvC) syndrome is a genetic disorder with mutations in either EVC or EVC2 gene. Previous case studies reported that EvC patients underwent orthodontic treatment, suggesting the presence of craniofacial bone phenotypes. To investigate whether a mutation in EVC2 gene causes a craniofacial bone phenotype, Evc2 knockout (KO) mice were generated and cephalometric analysis was performed. The heads of wild type (WT), heterozygous (Het) and homozygous Evc2 KO mice (1‐, 3‐, and 6‐week‐old) were prepared and cephalometric analysis based on the selected reference points on lateral X‐ray radiographs was performed. The linear and angular bone measurements were then calculated, compared between WT, Het and KO and statistically analyzed at each time point. Our data showed that length of craniofacial bones in KO was significantly lowered by ∼20% to that of WT and Het, the growth of certain bones, including nasal bone, palatal length, and premaxilla was more affected in KO, and the reduction in these bone length was more significantly enhanced at later postnatal time points (3 and 6 weeks) than early time point (1 week). Furthermore, bone‐to‐bone relationship to cranial base and cranial vault in KO was remarkably changed, i.e. cranial vault and nasal bone were depressed and premaxilla and mandible were developed in a more ventral direction. Our study was the first to show the cause‐effect relationship between Evc2 deficiency and craniofacial defects in EvC syndrome, demonstrating that Evc2 is required for craniofacial bone development and its deficiency leads to specific facial bone growth defect. Anat Rec, 299:1110–1120, 2016. © 2016 Wiley Periodicals, Inc.